Biodistribution and Immunogenicity of Allogeneic Mesenchymal Stem Cells in a Rat Model of Intraarticular Chondrocyte Xenotransplantation - Marquina, Maribel; Collado, Javier A.; Pérez-Cruz, Magdiel; Fernández-Pernas, Pablo; Fafián-Labora, Juan; Blanco, Francisco J.; Máñez, Rafael; Arufe, María C.; Costa, Cristina (Frontiers in Immunology, 2017)
Xenogeneic chondrocytes and allogeneic mesenchymal stem cells (MSC) are considered a potential source of cells for articular cartilage repair. We here assessed the immune response triggered by xenogeneic chondrocytes when injected intraarticularly, as well as the immunoregulatory effect of allogeneic bone marrow-derived MSC after systemic administration. To this end, a discordant xenotransplantation model was established by injecting three million porcine articular chondrocytes (PAC) into the femorotibial joint of Lewis rats and monitoring the immune response. First, the fate of MSC injected using various routes was monitored in an in vivo imaging system. The biodistribution revealed a dependency on the injection route with MSC injected intravenously (i.v.) succumbing early after 24 h and MSC injected intraperitoneally (i.p.) lasting locally for at least 5 days. Importantly, no migration of MSC to the joint was detected in rats previously injected with PAC. MSC were then administered either i.v. one week before PAC injection or i.p. 3 weeks after to assess their immunomodulatory function on humoral and adaptive immune parameters. Anti-PAC IgM and IgG responses were detected in all PAC-injected rats with a peak at week 2 post-injection and reactivity remaining above baseline levels by week 18. IgG2a and IgG2b were the predominant and long-lasting IgG subtypes. In contrast, no anti-MSC antibody response was detected in the cohort injected with MSC only, but infusion of MSC before PAC injection temporarily augmented the anti-PAC antibody response. Consistent with a cellular immune response to PAC in PAC-injected rats, cytokine/chemokine profiling in serum by antibody array revealed a distinct pattern relative to controls characterized by elevation of multiple markers at week 2, as well as increases in proliferation in draining lymph nodes. Notably, systemic administration of allogeneic MSC under the described conditions did not diminish the immune response. IL-2 measurements in co-cultures of rat peripheral blood lymphocytes (PBL) with PAC indicated that PAC injection induced some T-cell hyporesponsiveness that was not enhanced in the cohorts additionally receiving MSC. Thus, PAC injected intraarticularly in Lewis rats induced a cellular and humoral immune response that was not counteracted by the systemic administration of allogeneic MSC under the described conditions.